2013
DOI: 10.15580/gjas.2013.3.100613883
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship Development as a Strategy for Poverty Alleviation among Farming Households in Igbo-Eze North Local Government Area of Enugu State, Nigeria

Abstract: The emergence of the free market economies globally, has resulted in the development of a new spirit of enterprise and the increased farmer's need for more responsibility in running their farm business. Multistage random sampling technique was used to select a total of 120 respondents used for the study. Primary data were collected using structured questionnaires. Both descriptive and inferential statistics was used to achieve the objectives of the study. Results showed that the farmers are within the average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Findings also revealed that a little above average (51.7%) of the farmers engaged in trading as a form of secondary occupation while only a handful (11.7%) of them were not involved in any secondary occupation but solely depend on farming. The finding is in agreement with Mbam and Nwibo (2013) who reported that farmers engaged in various farm and non-farm activities as a way of income diversification which helps in reducing poverty among the farming household. Table 1 further showed that more than half (58.4%) of the farmers in the area are crop farmers implying that majority of the waste generated in the study area will be crop related as only few (35.8%) of the farmers are into livestock farming.…”
Section: Socio-economic Characteristics Of the Respondentssupporting
confidence: 91%
See 1 more Smart Citation
“…Findings also revealed that a little above average (51.7%) of the farmers engaged in trading as a form of secondary occupation while only a handful (11.7%) of them were not involved in any secondary occupation but solely depend on farming. The finding is in agreement with Mbam and Nwibo (2013) who reported that farmers engaged in various farm and non-farm activities as a way of income diversification which helps in reducing poverty among the farming household. Table 1 further showed that more than half (58.4%) of the farmers in the area are crop farmers implying that majority of the waste generated in the study area will be crop related as only few (35.8%) of the farmers are into livestock farming.…”
Section: Socio-economic Characteristics Of the Respondentssupporting
confidence: 91%
“…Also, livestock generate large amounts of wastes. Manure production can amount up to 5.27 kg/day/1000 kg live weight, on a wet weight basis (Mbam and Nwibo 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The marketing component of agripreneurship activities in Ebonyi State, Nigeria reveals that youths are mainly in marketing and distribution of cereals, legumes and nuts, livestock feed, palm products, cassava products and flour respectively. This justified the report of Mbam and Nwibo (2013) that the principal agricultural products marketed and distributed are cassava products, flour, confectionaries, palm products, rice, and yam. Meanwhile, they also involved in non-farm activities such as artisans, trading and agro-tourism.…”
Section: Resultsmentioning
confidence: 56%
“…A share of their current incomes could be channeled as capital investments into waste utilisation technology to enhance aggregate incomes and improve livelihoods. Mbam and Nwibo (2013) surmised that a combination of farm and nonfarm activities constitute sources of income for farmers which helps to lessen poverty among farm households.…”
Section: Discussionmentioning
confidence: 99%